A 2017 Horizon Scan of Emerging Issues for Global Conservation and Biological Diversity. (January 2017) - Sutherland, William J.; Barnard, Phoebe; Broad, Steven; Clout, Mick; Connor, Ben; Côté, Isabelle M.; Dicks, Lynn V.; Doran, Helen; Entwistle, Abigail C.; Fleishman, Erica; Fox, Marie; Gaston, Kevin J.; et al.
Abstract : We present the results of our eighth annual horizon scan of emerging issues likely to affect global biological diversity, the environment, and conservation efforts in the future. The potential effects of these novel issues might not yet be fully recognized or understood by the global conservation community, and the issues can be regarded as both opportunities and risks. A diverse international team with collective expertise in horizon scanning, science communication, and conservation research, practice, and policy reviewed 100 potential issues and identified 15 that qualified as emerging, with potential substantial global effects. These issues include new developments in energy storage and fuel production, sand extraction, potential solutions to combat coral bleaching and invasive marine species, and blockchain technology. Trends: This is the eighth such annual horizon scan. An international team with expertise in horizon scanning, science communication, and conservation research, practice, and policy identified 15 issues, following widespread consultation and a Delphi-like scoring process to identify the most important. The issues were wide ranging, and include sand extraction, blockchain technology, use of robotics to combat invasive species, and new developments in energy storage and fuel production.